Metacognitive strategy integration in formative assessment: validation of the MSI model for EFL listening - Helena Badu; Hasanuddin Fatsah; Karmila Machmud; Harto Malik (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
This study developed and validated a Metacognitive Strategy-Based Formative Assessment Model (MSI Model) for the Listening for Professional Context course at the English Education Study Program, Universitas Negeri Gorontalo. Employing Plomp’s Educational Design Research framework, the study addressed three research questions: (1) the current state of listening assessment practices, (2) the design of the MSI model and its integrated instruments, and (3) the content and construct validity of the model as evaluated by expert panels. Needs analysis data were gathered through document analysis of course syllabi and existing assessment instruments, semi-structured interviews with four lecturers, and questionnaires distributed to 40 students. The MSI model integrates a three-layered framework linking Planning, Monitoring,Evaluating (PME) metacognitive strategies with four formative assessment instruments: a PME metacognitive reflection rubric, a self-assessment checklist, a peer-assessment form, and a structured feedback protocol. Expert validation involving three specialists in educational methodology, language assessment, and EFL listening yielded a mean Content Validity Index (CVI) of 0.91 and Aiken’s V of 0.89, indicating strong content and construct validity. Qualitative feedback from experts highlighted the model’s conceptual coherence, and theoretical alignment. These findings indicate that the MSI model provides a theoretically grounded and expert-validated formative assessment framework for supporting metacognitive strategy integration in university-level EFL listening.